Faktor-Faktor yang Berhubungan dengan Pressure Injury pada Anak - Juairiah Juairiah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Children are vulnerable group to pressure injuries and has unique characteristics as associated factor. Factors related to pressure injury must be slightly different from adult. The intervention action considering the injury to the child must be specifically related to the factors associated with pressure in the child. The purpose of this study is to identify factors associated with PI in children. This study was carried out using systematic literature review studies. Articles for this study was obtained from Google scholar, Science-direct, PubMed, and Ebsco. Articles was published in 2009-2019 that discuss factors related to PI in children. The results of the study was factors related to PI in pediatric patients were divided into 3 categories, they were medical conditions, medical devices, and length of stay. Medical devices were direct trigger factors that causing PI in children. The most common medical devices identified in the study that causing PI were respiration aids such as ventilator. The medical condition was unpreventable factors of PI in children especially Multiple Organ Dysfunction (MODS) and comorbidities, as well as cardiovascular and respiratory disease. Long days of stay increase the risk of PI in children, importantly in the 7th day or more of stay. Prevention of PI in children must be done intensively and should be carried out according to the unique factors of the children group. Development of prevention bundles of PI in children must be done according to pediatric’s PI related factors. Keywords: child; medical devices; related factors; pressure injuries; pediatric ABSTRAK Anak merupakan kelompok yang rentan terhadap pressure injury dan memiliki karakteristik unik yang perlu diperhatikan. Tindakan intervensi pencegahan pressure injury pada anak harus spesifik terkait dengan faktor yang berhubungan dengan pressure injury pada anak. Tujuan dari studi ini adalah mengidentifikasi faktor yang berhubungan dengan PI pada anak. Studi ini merupakan studi Systematic Literature Review Artikel diperoleh dari Google scholar, Science-direct, PubMed, dan Ebsco. Artikel merupakan artikel yang terbit pada tahun 2009-2019 yang membahas faktor yang berhubungan dengan PI pada anak. Hasil studi mengidentifikasi faktor yang berhubungan dengan PI pasien anak adalah kondisi medis, alat medis, dan lama masa perawatan. Alat medis merupakan faktor pencetus terjadinya PI pada anak. Alat medis yang paling umum menyebabkan PI adalah alat bantuan respirasi seperti ventilator. Kondisi medis menjadi faktor yang tidak dapat dihindari menyebabkan PI pada anak teruatama kondisi medis multiple organ dysfunctions (MODS), kormobiditas, penyakit kardiovaskuler dan respirasi. Lama hari perawatan lebih dari 7 hari meningkatkan risiko PI pada anak. Pencegahan PI pada anak harus dilakukan secara intensif dan memperhatikan faktor unik dari kelompok anak. Pengembangan bundle pencegahan PI khusus untuk anak harus dilakukan agar intervensi dapat dilakukan sesuai dengan kelompok usia. Kata kunci: anak; alat medis; faktor yang berhubungan; pressure injury; pediatric